Identification of Saccharomyces cerevisiae Spindle Pole Body Remodeling Factors - Greenland, Kristen B. (Public Library of Science, 2010)
The Saccharomyces cerevisiae centrosome or spindle pole body (SPB) is a dynamic structure that is remodeled in a cell cycle dependent manner. The SPB increases in size late in the cell cycle and during most cell cycle arrests and exchanges components during G1/S. We identified proteins involved in the remodeling process using a strain in which SPB remodeling is conditionally induced. This strain was engineered to express a modified SPB component, Spc110, which can be cleaved upon the induction of a protease. Using a synthetic genetic array analysis, we screened for genes required only when Spc110 cleavage is induced. Candidate SPB remodeling factors fell into several functional categories: mitotic regulators, microtubule motors, protein modification enzymes, and nuclear pore proteins. The involvement of candidate genes in SPB assembly was assessed in three ways: by identifying the presence of a synthetic growth defect when combined with an Spc110 assembly defective mutant, quantifying growth of SPBs during metaphase arrest, and comparing distribution of SPB size during asynchronous growth. These secondary screens identified four genes required for SPB remodeling: NUP60, POM152, and NCS2 are required for SPB growth during a mitotic cell cycle arrest, and UBC4 is required to maintain SPB size during the cell cycle. These findings implicate the nuclear pore, urmylation, and ubiquitination in SPB remodeling and represent novel functions for these genes.